A New Approach to Research Ethics Using Guided Dialogue to Strengthen Research Communities - Mustajoki, Henriikka (Taylor & Francis, 2017)
Ethics and Academic Research examines both theories of ethical decision-making as well as apply those theories to a broad range of situations and questions within a research career and process. The focus is not only on what is wrong, or in doing the actual research, it is a broader perspective on how ethics can be a positive force in strengthening the research community. Offering valuable guidance to the researcher and ethical decision-maker, this will be an essential text for postgraduate students and senior academics invested in professional development and self-reflection.